Anti rheumatic herbal compound drug Yi Shen Juan Bi (YJB) as selective cytokines target in rheumatoid arthritis. Sri Lanka Journal of Indigenous Medicine - Perera, P. K.; Li, Y. (My University, 2011)
Objective: Present study was conduct to prepare dehydrated bee honey & garlic mix powder using an advanced drum drying technology and the formulation of novel dosage form (capsules) using the powder Methods: For above purpose, honey and garlic mix dehydrated using drum dryer and powder was capsulated in hard gelatinized capsules. Further, expression of its nutritional and medicinal value, this powder was analyzed for its moisture, protein, fat fiber and ash content, while analysis of active ingredients using thin layer chromatography (TLC). Results: The formulation was found to contain 3.87% moisture, 0.2% protein, 0.23% fat, 0.5213% of fiber, and 0.713% ash. Chemical analysis of the Madhu Lasuna powder showed that concentrations of active compounds were found significantly. The capsules sealed in air tight in cellophane pouches were not deteriorated and the quality of powder was kept high even after one year. Conclusions: In conclusion, dehydrated bee honey & garlic mix powder was more similar to its raw formula without lost its nutritional and medicinal value. Also it is now consumer desired product.